FRAMING INCLUSIVITY: A PHOTOVOICE EXPLORATION OF DISABILITY ACCOMMODATIONS IN SANATA DHARMA UNIVERSITY - Kurniastuti, Irine; Sumarah, Ignatia Esti; Winarti, Eny (Sanata Dharma University Yogyakarta, 2025)
The voices of students with disabilities in inclusive higher education have not been widely revealed. This study aims to capture the learning experience in inclusive higher education using the photovoice method involving students with disabilities (Deaf and autistic) and their student companions. The activities carried out are emphasized so that the subjects convey their aspirations. Subjects are asked to photograph, record, and reflect on their experiences of good practices in inclusive learning, concerns experienced, and suggestions for improvement. The problems experienced are problems regarding accessibility, availability of infrastructure, understanding of deaf and autistic culture, and career problems. Furthermore, a critical dialogue is carried out to reach policy makers at the university and efforts to provide better inclusive education services.